PASSIVE DOSIMETRY: COMPARATIVE STUDY BETWEEN TWO EVALUATION METHODS OF OCCUPATIONAL EXPOSURE TO PESTICIDES - Pinheiro, Francisco Alves; do Egito, José Lourenço; Adissi, Paulo José (International Journal of Research -GRANTHAALAYAH, 2019)
The present study aims to compare the passive dosimetry sampling and census methods for the evaluation of pesticide exposure. The studies were carried out in the city of Petrolina - PE, in the São Francisco River Valley, under three working conditions: weeds, grape and acerola cultivation with the use of a hand-held sprayer in the Brazilian summer. For data analysis, descriptive statistical parameters and Student's T-test were used to compare the means of paired samples. Both methods evaluated the simulated manual application of pesticides. Given the results, it was concluded that there was a high discrepancy between exposure assessments in all treatments, with the sample method showing overestimated values, with differences greater than 200% and that the census method showed more reliable and accurate results with greater efficiency.